Preparation and characterization of asymmetric chitosanbiogenic hydroxyapatite composite membrane for guided bone regeneration - Bee, Soo Ling (2019)
Membranes used in guided bone regeneration (GBR) application serve as a physical barrier to prevent the migration of epithelial cell into the defected site before new bone formation occurs. The objective of this research is to prepare asymmetric membrane based on the combination of chitosan (CS) and biogenic hydroxyapatite (HA) for GBR. Briefly, HA with optimum compositional, structural and morphological properties was successfully extracted from chicken bone waste via calcination process at temperature of 600 oC and 20 h of calcination time. Thereafter, the prepared HA was incorporated into CS to form CS/HA composite membrane, where the impact of filler loading (10-50 phr of HA) and NaOH treatment on the characteristics of resulting membranes were evaluated with respect to surface morphology, structural change, hydrophilicity, mechanical property, antimicrobial property, swelling behavior, protein adsorption, degradation and in vitro bioactivity. Scanning electron microscopy (SEM) revealed that all composite membranes displayed an asymmetric smooth-rough surface, in which the coarseness of the rough surface increased when the HA content was increased. Furthermore, increasing HA loading also enhance the protein adsorption capability of the resulting membranes. Meanwhile, HA-incorporated membrane exceeding 10 phr loading exhibited improved bioactivity in comparison with pristine CS sample, which able of developing apatitic layer after 4 weeks of soaking in simulated body fluid. On the other hand, it was revealed that NaOH treatment improve water resistance and mechanical properties of all membranes, however, it had unfavourably diminish their antimicrobial ability. Overall, all membranes degraded less than 22 % of the initial weight after 2 months of incubation period, where their degradation rate decrease further as HA loading increase. These findings demonstrate the feasibility of chicken bone-derived HA to be employed as bioactive filler to augment and tailor the biological characteristics and degradation behavior of CS membrane for GBR application.